Efficacy Of Intravaginal Progestogen Sponges For Oestrus Syncronization In Goats - Pawshe, M.D.; Ingawale, M.V.; Pawshe, C.H.; Deshmukh, S.G.; Munde, V.K.; Kharche , S.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was carried out to evaluate the efficacy of intravaginal progestogen sponges for oestrus synchronization in goats under field condition. Intravaginal progestogen sponges were inserted in 24 randomly selected non pregnant goats which were divided equally into two groups (Group I and Group -II). In both the groups injection CIRG 1 ml was administered intramuscularly on day of sponge insertion. Injection equine chorionic gonadotropin (eCG) 400 IU was administered intramuscularly on day nine (D=9) to the goats in Group-II only. While injection Cloprostenol sodium 263 µg/ml was administered intramuscularly and sponges were removed from all the experimental goats on day ten (D=10). The goats were observed for oestrus exhibition from 11th to 14th day and mated with fertile bucks. All the 24 sponges inserted were retained in the vaginal passage till removed. The time interval for onset of oestrus was significantly (P<0.05) shorter in Group-II (17.41 ± 1.31 vs 20.91 ± 0.27 hrs). Pregnancy rate in oestrus synchronized goats was 33.33 and 25.00 per cent, in Group- I and II respectively which did not differ significantly (P<0.05).